2020
DOI: 10.3390/vaccines8020326
|View full text |Cite
|
Sign up to set email alerts
|

IFN-I Independent Antiviral Immune Response to Vesicular Stomatitis Virus Challenge in Mouse Brain

Abstract: Type I interferon (IFN-I) plays a pivotal role during viral infection response in the central nervous system (CNS). The IFN-I can orchestrate and regulate most of the innate immune gene expression and myeloid cell dynamics following a noncytopathic virus infection. However, the role of IFN-I in the CNS against viral encephalitis is not entirely clear. Here we have implemented the combination of global differential gene expression profiling followed by bioinformatics analysis to decipher the CNS immune response… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 55 publications
0
10
0
Order By: Relevance
“…This could exacerbate pathogenesis of lung parenchymal cells, diminish oxygen uptake, and cause rapid thrombotic events and intravascular coagulation, which could result in multiorgan failure including central nervous system complications and death. [54] …”
Section: Discussionmentioning
confidence: 99%
“…This could exacerbate pathogenesis of lung parenchymal cells, diminish oxygen uptake, and cause rapid thrombotic events and intravascular coagulation, which could result in multiorgan failure including central nervous system complications and death. [54] …”
Section: Discussionmentioning
confidence: 99%
“…Single cell or snRNAseq is a useful tool to study the transcriptional response in specific cell types upon infection or inflammation. In contrast to bulk RNA sequencing or microarray analysis of tissue 56,57 , where the combined response of all cells is measured, we show that in WT mice, the response to infection was highly cell-type specific and that the identified upregulated pathways showed a balance between pro-and anti-inflammatory signaling. While scRNA sequencing of Rabies virus infected WT mice showed a very strong pro-inflammatory response 58 , we detected a relatively low number of DEGs after LGTV infection in WT mice.…”
Section: Discussionmentioning
confidence: 61%
“…Even though we detected a similar viral load in cerebral cortex of WT and Ifnar –/– mice, the transcriptional profiles were markedly different, and a large number of DEGs were upregulated independently of IFNAR signaling. This IFN-I-independent immune response has also been observed for vesicular stomatitis virus (VSV) 56 . In this case, IFNγ in combination with TNFα and IRF1 compensate for the loss of IFN-I response 56 .…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…Although Vero cells lack the ability to produce IFN [5] , there might be other IFN-independent innate immune pathways that lactate is modulating. It has been shown that VSV infection modulates many genes even in the absence of IFN signaling [21] . It is plausible that with its role in both cell metabolism and innate immune signaling, increased initial levels of lactate in bioreactors without MX have “primed” the cells for a favorable viral replication environment.…”
Section: Resultsmentioning
confidence: 99%